2016
DOI: 10.1111/jam.13072
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial indicator taxa in soils under different long-term agricultural management

Abstract: In this study, we report that agricultural practice affected soil bacterial communities. We also identified distinctive taxa and related their distribution to changes in the soil environment resulting from different agricultural practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 61 publications
6
26
0
Order By: Relevance
“…In agreement with the first hypothesis of our study, the tillage regime was a significant driver of microbial β-diversity ( Figure 1A and Tables 2 , 3 ), which is consistent with the recent literature using high-resolution techniques (Quadros et al, 2012; Navarro-Noya et al, 2013; Carbonetto et al, 2014; Sengupta and Dick, 2015; Degrune et al, 2016; Jiménez-Bueno et al, 2016). However, the direction of change of some microbial groups was not consistent with the other studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with the first hypothesis of our study, the tillage regime was a significant driver of microbial β-diversity ( Figure 1A and Tables 2 , 3 ), which is consistent with the recent literature using high-resolution techniques (Quadros et al, 2012; Navarro-Noya et al, 2013; Carbonetto et al, 2014; Sengupta and Dick, 2015; Degrune et al, 2016; Jiménez-Bueno et al, 2016). However, the direction of change of some microbial groups was not consistent with the other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported effects of soil tillage and/or crop residue management on soil microbial community structures (Quadros et al, 2012; Navarro-Noya et al, 2013; Carbonetto et al, 2014; Sengupta and Dick, 2015; Degrune et al, 2016; Jiménez-Bueno et al, 2016). For example, the diversity of arbuscular mycorrhizal fungi (AMF), a group of fungi supporting the host plant with enhanced nutrient acquisition and increased resistance against drought and root pathogens (Van Der Heijden et al, 1998), has shown to be increased under reduced tillage (Säle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These investigations have identified that microbial attributes could reflect ecosystem processes such as crop productivity [3], the regulation of decomposition [4], nutrient cycling [5] and protection against soil-borne pathogens [6]. Several studies have shown that agricultural Sustainability 2018, 10, 3825 2 of 16 practices have significant influences on soil microbial communities and composition, including the tillage regime [7], fertilization [8], monoculture [9], crop residue management [10] and plant protection schemes [11]. Hence, the soil microbial community could be shifted to a positive organization for plant production and ecosystem sustainability by suitable agricultural practices [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, high microbial diversity has been linked to high functional diversity in soil [5], which may cause the important ecological processes mentioned above. In addition, most researchers studied the microbial community under different agricultural management practices with field crops such as rice [3,21] and wheat [10], whereas little research has focused on vegetable cultivations [22]. Specifically, we still have a limited understanding of the long-term effects of organic and conventional management on soil microbial communities under open-field and protected conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundances of individual phyla in different samples were computed by R packages. The indicator analysis based on genera-specific to each soil depth was conducted using indicspecies package of R with 9999 permutations, and the P-values were corrected for multiple testing using qvalue package of R(14, 66). Functional profiles of the microbial community were predicted by Tax4fun (an open-source package in R)(67) and further statistical analysis was conducted by STAMP using Welch’s t-test(68).…”
Section: Methodsmentioning
confidence: 99%